Relationship between solid state structure and solution stability of copper(ii)–hydroxypyridinecarboxylate complexes. (20th June 2019) - May, Nóra V.; Gál, G. Tamás; Szentendrei, Zsolt; Korecz, László; May, Zoltán; Ferlin, Maria Grazia; Dean, Annalisa; Bombicz, Petra; Di Marco, Valerio B.
Abstract : More acidic –OH groups increase the solution stability of copper(ii )–hydroxypyridinecarboxylate complexes and they lose the bridging role in cyclic dimer formation. Abstract : The complementary solid state/solution studies of the systematic series of bioactive ligands 3-hydroxy-1-methyl-4-pyridinecarboxylate (L1 ), 3-hydroxy-1, 2, 6-trimethyl-4-pyridinecarboxylate (L2 ), 4-hydroxy-1-methyl-3-pyridinecarboxylate (L3 ), 4-hydroxy-1, 6-dimethyl-3-pyridinecarboxylate (L4 ), 4-hydroxy-1-(2-hydroxyethyl)-6-methyl-3-pyridinecarboxylate (L5 ) and 4-hydroxy-1-(2-carboxyethyl)-6-methyl-3-pyridinecarboxylate (L6 ) with copper(ii ) have been performed in order to design efficient chelating drugs for the treatment of metal overloading conditions. Single crystals of [Cu(L1 )2 (H2 O)]·3H2 O (1 ) (monomer) with axial water coordination, [Cu2 (L2 )4 ]·6H2 O (2 ) and [Cu2 (L3)4 ]·4H2 O (3 ) (cyclic dimers), where pyridinolato and carboxylato oxygens, respectively, act as linkers between adjacent copper complexes, [Cu(L4 )2 ] n ·3H2 O (4 ) (1D polymer) and [Cu3 (L5 )6 ]·18H2 O (5 ) (trimer), constructed using two square-pyramidal and one elongated octahedral Cu(ii ) complexes have been determined by SXRD. The bidentate coordination mode of the ligands has been found preferentially with cis arrangements in1 and2 and trans arrangements in3–5 . The solution speciation and complex stability of aqueous solutions have been studied by pH-dependent electron paramagnetic resonance spectroscopy resulting in the detection of solely monomeric [CuL] + and [CuL2 ] complexes. The stability order obtained for the [CuL] + complexes could be correlated with the deprotonation constants of their hydroxyl group (log β LH ) reflecting that the higher acidity increases the complex stability in the orderL2 <L1 ≈L6 <L4 ≈L5 <L3 . This stability order elucidates the different axial linkers in the cyclic dimers2 and3 . DFT quantum-chemical calculations support the effect of the electron distribution on the established stability order.